Microstrip Patch Antennas with Anisotropic and Diamagnetic Synthetic Heterogeneous Substrates - Data Set - Chinwe Njoku; Will Whittow; Yiannis C. Vardaxoglou (2015)
Figure showing frequency response for patch on heterogeneous material with metallic inclusions in different orientations.